1996
DOI: 10.1007/bf01271187
|View full text |Cite
|
Sign up to set email alerts
|

Histaminergic modulation of neocortical spindling and slow-wave activity in freely behaving rats

Abstract: Histaminergic H3 receptor antagonists stimulate neuronal histamine release and could consequently have a number of physiological effects in the brain. The effects of H3 receptor blockade, induced by systemically administered thioperamide, were assessed on the frontal cortex electroencephalographic (EEG) properties in freely behaving rats. The relationship of EEG activity variables to endogenous brain histaminergic markers was also examined, both in controls and in portocaval anastomosis (PCA)-operated rats (wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…12,17 Furthermore, the spontaneous, as well as the depolarizationinduced and pharmacologically induced histamine release from anterior hypothalamus are significantly increased in these rats. 17 Histamine, through the activation of postsynaptic H 1 receptors, is involved in the regulation of the mechanisms of arousal, 19,20 locomotor activity, [21][22][23][24] feeding behavior, and energy balance, 25,26 and circadian rhythmicity (for reviews, see Tuomisto 27 and Nowak 28 ). We have previously suggested that histaminergic synaptic imbalance may have contributed to the sleep disturbances in rats with PCA.…”
mentioning
confidence: 99%
“…12,17 Furthermore, the spontaneous, as well as the depolarizationinduced and pharmacologically induced histamine release from anterior hypothalamus are significantly increased in these rats. 17 Histamine, through the activation of postsynaptic H 1 receptors, is involved in the regulation of the mechanisms of arousal, 19,20 locomotor activity, [21][22][23][24] feeding behavior, and energy balance, 25,26 and circadian rhythmicity (for reviews, see Tuomisto 27 and Nowak 28 ). We have previously suggested that histaminergic synaptic imbalance may have contributed to the sleep disturbances in rats with PCA.…”
mentioning
confidence: 99%
“…9,11 One of the most striking consequences of the PCA surgery in rats is the remarkable elevation of brain histamine levels, which appears as early as 10 days, and persists for at least 8 months after PCA surgery. [12][13][14][15] The significance of this observation for the pathogenesis of PSE, however, has not been studied in detail.Histaminergic neurons in the mammalian brain are thought to play a role in the control of vigilance, sleep, and wakefulness, [16][17][18][19][20][21] and in the modulation of circadian rhythmicity. 22 The role of histaminergic mechanisms in the control of the sleep-wakefulness continuum in humans has also been confirmed.…”
mentioning
confidence: 99%
“…23,24 Furthermore, earlier studies have demonstrated a correlation between the sleep disturbances and brain histamine levels in rats with PCA. 21,25 Because histamine has a well-known physiological role in the modulation of sleep behavior and circadian rhythms, we have now attempted to find out whether the increased brain levels of histamine in PCA-operated rats are associated with changes in the sleep patterns of these rats during the light phase. Because such changes cannot be detected by simple observation, we used electroencephalographic (EEG) recordings from the frontal cortex of freely behaving rats as brain-state markers to discriminate sleep, drowsiness, and wakefulness.…”
mentioning
confidence: 99%
See 2 more Smart Citations